The Configuration of Electoral Design in Indonesia Following the Constitutional Court Decision Number 135/PUU-XXII/2024 Concerning the Separation of the Implementation of National Elections and Local Elections - Bangas, Karlinae D.; Susilowati, Eny; Safari, Fuji Syifa (SEAN Institute, 2025)
This study examines the implications of the Constitutional Court Decision No. 135/PUU-XXII/2024 concerning the separation of National and Local Elections in Indonesia. The separation introduces significant normative, institutional, fiscal, and socio-political challenges, including potential judicial overreach, administrative burdens, fragmentation of governance cycles, and decreased political participation. This research employs doctrinal legal analysis with statute, case, conceptual, and comparative approaches, aiming to analyze both normative aspects and practical consequences of the election separation. The findings indicate that post-decision electoral design must ensure legal certainty through legislative revisions, strengthen the capacity of election management institutions, and enhance political representation and public participation. Comparative studies with India and the United States demonstrate that separated elections can operate effectively without reducing legitimacy, provided legal, institutional, and public participation frameworks are properly established. The ideal configuration is for national and local elections to remain within a single five-year governmental period, but conducted with planned temporal intervals to substantively and sustainably reinforce constitutional democracy.